2016
DOI: 10.4236/aim.2016.67049
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug Resistant Acute Otitis Media amongst Children Attending Out-Patient Clinic in Chukwuemeka Odumegwu Ojukwu University Teaching Hospital, Awka, South-East Nigeria

Abstract: Objective: The study assessed microbial etiology and multi-drug resistant profile of the pathogens isolated from children diagnosed of acute otitis media (AOM) at Chukwuemeka Odumegwu Ojukwu University Teaching Hospital, Awka. Method: Ear swab samples were collected aseptically from 40 children that visited the children out-patient clinic of the hospital. The samples were cultured within 20 minutes of collection and the isolates identified microbiologically. Antimicrobial susceptibility testing was done by Kir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
4
9
0
Order By: Relevance
“…aureus was the commonest isolate in our study similar to the findings by Iraq (Al-Marzoqi et al, 2013) and Ehiopia (Wasihun and Zemene, 2015). P. aeruginosa was the commonest Gram negative isolate similar to findings in many studies (Nnebe-Agumedu et al, 2011;Afolabi et al, 2012;Jido et al, 2014;Es-Said et al, 2014;Elmanama et al, 2014;Wasihun and Zemene, 2015;Garima et al, 2016;Ejiofor et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…aureus was the commonest isolate in our study similar to the findings by Iraq (Al-Marzoqi et al, 2013) and Ehiopia (Wasihun and Zemene, 2015). P. aeruginosa was the commonest Gram negative isolate similar to findings in many studies (Nnebe-Agumedu et al, 2011;Afolabi et al, 2012;Jido et al, 2014;Es-Said et al, 2014;Elmanama et al, 2014;Wasihun and Zemene, 2015;Garima et al, 2016;Ejiofor et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Another reason for the low number of ear discharge samples could be due to lack of an ear, nose and throat specialist and clinic in our hospital; hence, children with otitis media are more likely to seek medical attention at a tertiary hospital in the state where such services are available. Majority of the children were below five years of age which is similar to the findings in Abakaliki (NnebeAgumedu et al, 2011), Zaria (Jido et al, 2014), Rabat (Es-Said et al, 2014), and Awka (Ejiofor et al, 2016). There were more males in the study although not significant, which was similar to the findings in Abakaliki (Nnebe-Agumedu et al, 2011), Ilorin (Afolabi et al, 2012), and other studies (El-Manama et al, 2014;Garima et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The incidence of resistant Escherichia coli in the study center has been reported by other researchers [31, 32] who demonstrated the presence of ESBL producing Escherichia coli .…”
Section: Discussionsupporting
confidence: 72%